Problems of Certain Aspects of Military Education in the Course of Combat Training Development - Golubenko Alexey Yurievich (Zien Journals, 2022)
The article reveals the problematic issues that exist at the present stage of development of combat training based on the experience of foreign experts in this field, based on the practical experience of modern armed conflicts.
Keywords: tactics; foreign experience; terrorist organizations; psychological readiness